TSG-6 Inhibits Oxidative Stress and Induces M2 Polarization of Hepatic Macrophages in Mice With Alcoholic Hepatitis via Suppression of STAT3 Activation - Wan, Yue-Meng; Wu, Hua-Mei; Li, Yu-Hua; Xu, Zhi-Yuan; Yang, Jin-Hui; Liu, Chang; He, Yue-Feng; Wang, Men-Jie; Wu, Xi-Nan; Zhang, Yuan (Frontiers in Pharmacology, 2020)
Abstract Tumor necrosis factor (TNF)-α-stimulated protein 6 (TSG-6) is a secreted protein with diverse tissue protective and anti-inflammatory properties. We aimed to investigate its effective in treating mice with alcoholic hepatitis (AH) and the associated mechanisms. AH was induced in 8-10 week female C57BL/6N mice by chronic-binge ethanol feeding for 10 days. Intraperitoneal (i.p.) injection of recombinant mouse TSG-6 or saline were performed in mice on day 10. Blood samples and hepatic tissues were collected on day 11. Biochemistry, liver histology, flow cytometry and cytokine measurements were conducted. Compared to the normal control mice, the AH mice had significantly increased liver/body weight ratio, serum alanine aminotransferase (ALT) and aspartate aminotransferases (AST), hepatic total cholesterol (TC), triglyceride (TG), malondialdehyde (MDA), hepatic macrophage infiltration, serum and hepatic interleukin (IL)-6, and tumor necrosis factor (TNF)-α, which were markedly reduced by i.p. injection of rmTSG-6. Compared to the normal control mice, the hepatic glutathione (GSH), accumulation of M2 macrophages, serum and hepatic IL-10 and TSG-6 were prominently reduced in the AH mice, which were significantly enhanced after i.p. injection of rmTSG-6. Compared to the normal control mice, hepatic activation of signal transducer and activator of transcription 3 (STAT3) was significantly induced, which was markedly suppressed by rmTSG-6 treatment. TSG-6 were effective for the treatment of AH mice, which might be associated with its ability in inhibiting hepatic oxidative stress and inducing hepatic M2 macrophages polarization via suppressing STAT3 activation.